KEY FEATURES OF THE POETICS OF RUSSIAN PROVERBS - Arslanova Mohiroy Odiljanovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article provides a detailed analysis of some characteristics of proverbs and sayings. A proverb and a saying are a short folk saying with edifying content.